2014
DOI: 10.1186/1750-1172-9-86
|View full text |Cite
|
Sign up to set email alerts
|

Parkin-mediated ubiquitination of mutant glucocerebrosidase leads to competition with its substrates PARIS and ARTS

Abstract: BackgroundParkinson’s disease (PD) is a movement neurodegenerative disorder characterized by death of dopaminergic neurons in the substantia nigra pars compacta of the brain that leads to movement impairments including bradykinesia, resting tremor, postural instability and rigidity. Mutations in several genes have been associated with familial PD, such as parkin, pink, DJ-1, LRKK2 and α-synuclein. Lately, mutations in the GBA gene were recognized as a major cause for the development of PD.Mutations in the GBA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…This effect may be attributed to the ER retention of mutant GBA protein, resulting in an unfolded protein response [67,68]. For example, N370S and L444P GBA mutant proteins, but not WT GBA, interact with PRKN/PARK2 within the ER [69], preventing the binding of PRKN/PARK2 to other substrates [70]. …”
Section: Discussionmentioning
confidence: 99%
“…This effect may be attributed to the ER retention of mutant GBA protein, resulting in an unfolded protein response [67,68]. For example, N370S and L444P GBA mutant proteins, but not WT GBA, interact with PRKN/PARK2 within the ER [69], preventing the binding of PRKN/PARK2 to other substrates [70]. …”
Section: Discussionmentioning
confidence: 99%
“…The fact that Hsp27 recruitment was significantly diminished in nonfunctional Hsp90 mutants confirmed that proper Hsp90 biologic function was integral to recognition and degradation of mutant GCase. GCase mutants are heavily ubiquitinated and degraded (7,19), a process that depends upon involvement of the Hsp90 complex (13). The mutant-specific recruitment of Hsp27 to the Hsp90 chaperone complex suggested that Hsp27 was related to the ubiquitination and degradation of mutant GCase.…”
Section: Significancementioning
confidence: 99%
“…Moreover, Ballabio's group has shown that mTOR, one of GSK3 downstream target kinases, interacts with and phosphorylates TFEB on the lysosomal membrane, thereby preventing its translocation to the nucleus, further indicating a connection between these pathways (Settembre et al, 2012). In parallel, parkin, a PD-related E3 ubiquitin ligase whose expression is regulated also by ER stress (Bouman et al, 2011), is involved in mitophagy (Calì et al, 2013) and in the ubiquitination and proteasomal degradation of several substrates, including mutant GCase (Ron et al, 2010;Bendikov-Bar et al, 2014).…”
Section: Introductionmentioning
confidence: 99%